TINGKAT KEPATUHAN PASIEN TB PARU TERHADAP PENATALAKSANAAN PROGRAM OAT (OBAT ANTI TUBERKULOSIS) DI POLIKLINIK PARU RSUD SANJIWANI GIANYAR - Ni Kadek Ayu Patni Dewi; Ni Made Diah P Pendet; I Made Sukarja; Ni Made Wina Krisnayani (Jurnal Kesehatan Medika Udayana, 2018)
Introduction :Tubercolosis (TB) diseases is one of the most public health problems in Indonesia. Indonesia known as a the third highest of TB cases in the world after India and China. In 2010, the Ministry of Health In Indonesia reported that patient with TB in worldwide about 5,8 % cases was found in Indonesia. In Indonesia, TB drugs treatments called the OAT Program. The study about the interpersonal factors who can be related to the compliance of patient with TB determined how important the role of doctors and other health professionals to do verbal and non verbal communication with patients. The aim of this study was to describe complianced of patient with TB in OAT program at Sanjiwani general hospital, Gianyar. Method : This was observational descriptive study. Data were collected through questionnaires. The total of patient with TB who participated in this research were 78 collected by consecutive sampling technique. Result :Based on the research, the complianced of patient with TB in OAT program showed that 38 respondent (48,71%) had complianced with the OAT program and 40 respondent (51,28 %) didn’t have compliance with the OAT program. Conclusion :Most of the patient with TB in Sanjiwani general hospital didn’t have compliance with OAT program.Key words: Compliance; OAT program; Tubercolosis.